In Ovo and Oral Administration of Probiotic Lactobacilli Modulate Cell- and Antibody-Mediated Immune Responses in Newly Hatched Chicks - Alizadeh, Mohammadali; Bavananthasivam, Jegarubee; Shojadoost, Bahram; Astill, Jake; Taha-Abdelaziz, Khaled; Alqazlan, Nadiyah; Boodhoo, Nitish; Shoja Doost, Janan; Sharif, Shayan (Frontiers in Immunology, 2021)
Abstract There is some evidence that lactobacilli can strengthen the immune system of chickens. This study evaluated the effects of in ovo and oral administration of a lactobacilli cocktail on cytokine gene expression, antibody-mediated immune responses, and spleen cellularity in chickens. Lactobacilli were administered either in ovo at embryonic day 18, orally at days 1, 7, 14, 21, and 28 post-hatches, or a combination of both in ovo and post-hatch inoculation. On day 5 and 10 post-hatch, spleen and bursa of Fabricius were collected for gene expression and cell composition analysis. On days 14 and 21 post-hatch, birds were immunized with sheep red blood cells (SRBC) and keyhole limpet hemocyanin (KLH), and sera were collected on days 7, 14, and 21 post-primary immunization. Birds that received lactobacilli (107 CFU) via in ovo followed by weekly oral administration showed a greater immune response by enhancing antibody responses, increasing the percentage of CD4+ and CD4+CD25+ T cells in the spleen and upregulating the expression of interferon (IFN)-α, IFN-β, interleukin (IL)-8, IL-13, and IL-18 in the spleen and expression of IFN-γ, IL-2, IL-6, IL-8, IL-12, and IL-18 in the bursa. These findings suggest that pre-and post-hatch administration of lactobacilli can modulate the immune response in newly hatched chickens.